ANALISIS DROP CALL PADA JARINGAN WIDEBAND CODE-DIVISION MULTIPLE ACCESS (WCDMA) DI CLUSTER RENON - Surya Winata, I Gusti Ngurah; Sukadarmika, Gede; Sudiarta, Pande Ketut (Jurnal SPEKTRUM; Vol 6 No 1 (2019): Jurnal SPEKTRUM, 2019)
Drop call is an example of a problem that is often experienced by users of voice telecommunications services. From this condition, this riset raises the topic of drop call analysis on WCDMA networks in the Renon cluster (nodeB MYAMIN_CR, AKABA_PL, and BUNDARANRENON_PL). Data retrieval needed (Call Set Up Success Rate (CSSR), Call Drop Ratio (CDR), RSCP and Ec/No) is done by drive test using G-NetTrack Pro software. Based on the analysis of the results of the drive test, there were 10 drop call problems. The problems indentified cause by missing neighbors, handover failure, bad spot, coverage problems and overshoot. Bad spots, coverage problems, and overshoot are the initial causes of missing neighbors and handovers failure. Missing neighbors and handover failure begins with the poor value of RSCP and Ec/No, so that the cellphone will try to do a handover. To analyze the drive test results, drive test data is carried out using Atoll software. From the comparison found extreme conditions resulting from obstacle which cause a significant difference in value between the results of the drive test and simulation. The high attenuation rate drop call location due to the obstacle also results in RSCP and Ec/No values being obtained when measurements in the field are low. The low parameter values of RSCP and Ec / No then cause a drop call.